Measuring Energy Supply Risks: A G7 Ranking - Manuel Frondel; Nolan Ritter; Christoph M. Schmidt (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2009)
The security of energy supply has again become a similarly hot topic as it was during the oil crises in the 1970s, not least due to the recent historical oil price peaks. In this paper, we analyze the energy security situation of the G7 countries using a statistical risk indicator and empirical energy data for the years 1978 through 2007. We find that Germany's energy supply risk has risen substantially since the oil price crises of the 1970s, whereas France has managed to reduce its risk dramatically, most notably through the deployment of nuclear power plants. As a result of the legally stipulated nuclear phase-out, Germany's supply risk can be expected to rise further and to approach the level of Italy. Due to its resource poverty, Italy has by far the highest energy supply risk among G7 countries.
Keywords: C43; Q41; 330; Herfindahl Index; Energy Supply Risk Indicator; Energieversorgung; Risiko; Deutschland